"Short and Sweet": A Randomized Controlled Initial Investigation of Brief Online Psychological Interventions With Endurance Athletes - Meijen, C.; McCormick, A.; Anstiss, P. A.; Marcora, S. M. (The Sport Psychologist, 2022)
There is potential in delivering brief, educational interventions online, particularly for recreational athletes. This initial investigation examined how two online interventions were perceived by endurance participants and how they affected outcomes of interest. After measuring self-efficacy, 142 people were randomized to one of three groups (self-talk, implementation intentions, and control) before an endurance event. Ninety-four completed postevent measures, which were self-efficacy, goal attainment, performance satisfaction, coping, stress appraisals, and social validity. The interventions involved approximately 10 min of initial engagement with online material. Perceptions of stress controllability were significantly higher in the implementation intention group compared with the control. There were no other statistically significant effects. Nevertheless, both intervention groups were satisfied with their interventions, found them useful, and were planning to continue using them. The findings demonstrate the feasibility and value of using brief, online psychological interventions, which may be timely in our changing profession, as COVID-19 has moved many interventions online.